From East to West: Carl W. Ernst's insight into sufism's impact on islamic studies in America - Hasyim, Fuad; Ningrum, Nur Sakti; Lukito , Ratno (IJISH (International Journal of Islamic Studies and Humanities), 2024)
With its global expansion and incorporation of elements from other religions, Sufism presents an intriguing field of study for Western scholars interested in the mystical and societal influence of Islam. This article aims to explore the impact of Sufism on existing Islamic studies in America. The study adopts a qualitative approach, relying on library research to analyze the origin, development, and evolution of ideas through the works of Carl W. Ernst. The research findings demonstrate that Sufism has had a significant impact on the advancement of Islamic studies, particularly in fostering a deeper understanding and respect between American society and Muslims. By promoting love, compassion, and unity, Sufism plays a vital role in bridging misconceptions and facilitating peaceful coexistence.